Muscle biopsy and UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase gene mutation analysis in two Chinese patients with distal myopathy with rimmed vacuoles. Issue 10 (8th July 2015) - Liu, Nan; Wang, Zhong-Kun; Wang, Hai-Xia; Li, Yan; Niu, Zhen-Hua; Yu, Xue-Fan
<x xml:space="preserve">Abstract</x> Distal myopathy with rimmed vacuoles is an autosomal recessive genetic disease characterized by weakness of the anterior compartment of the lower limbs, sparing the quadriceps muscle, and rimmed vacuoles in muscle biopsies. The disease is caused by a mutation in the UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE) gene located on chromosome 9p13.3. We present two cases of Chinese patients with progressive lower extremity weakness. Clinical presentation, laboratory evaluation, electrodiagnostic testing, muscle pathology, and genetic analysis are described. Patient 1 was found to have heterozygous missense mutations (p.C13S and p.G576R) in the GNE gene and patient 2 had a homozygous missense mutation (p.C13S). The mutation p.C13S has been reported previously in China, Japan, and South Korea; however, the mutation p.G576R has not been described previously.